1997
DOI: 10.2307/2446077
|View full text |Cite
|
Sign up to set email alerts
|

Extreme preformation in alpine Polygonum viviparum: an architectural and Developmental Analysis

Abstract: Preformation, the initiation of organs one or more years prior to maturation and function, is reported to be common and crucial for plant survival in arctic and alpine environments, yet the phenomenon is remarkably little studied. In order to understand the role of preformation in the ecology and evolution of tundra species, this investigation takes a developmental and architectural approach to the analysis of plant growth and reproduction in the alpine perennial Polygonum viviparam L. Analyses show that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
143
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(143 citation statements)
references
References 56 publications
0
143
0
Order By: Relevance
“…In inherently poor and stress affected habitats, such as high-salt meadows, selection may favor plants with weak plasticity in growth and morphology (Van Groenendael & De Kroon 1990;De Kroon & van Groenendael 1997;. Also, in cold tundra environments, individual phenotypic plasticity is predicted to be low (Grime 1977 ;Fetcher & Shaver 1990;Chapin et al 1993;Diggle 1997), probably because the cost of plasticity in growth and morphology in such environment are very high (Hutchings & De Kroon 1994). In alpine environments, in particular low soil temperature is the major constraint for the supply of plants with available nitrogen (Bliss 1971).…”
Section: Discussionmentioning
confidence: 99%
“…In inherently poor and stress affected habitats, such as high-salt meadows, selection may favor plants with weak plasticity in growth and morphology (Van Groenendael & De Kroon 1990;De Kroon & van Groenendael 1997;. Also, in cold tundra environments, individual phenotypic plasticity is predicted to be low (Grime 1977 ;Fetcher & Shaver 1990;Chapin et al 1993;Diggle 1997), probably because the cost of plasticity in growth and morphology in such environment are very high (Hutchings & De Kroon 1994). In alpine environments, in particular low soil temperature is the major constraint for the supply of plants with available nitrogen (Bliss 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis I also indicated that a shift occurred over the first 3-4 years of warming from strong vegetative responses early on toward greater reproductive effort and success in the fourth treatment year (Arft et al 1999). These results were interpreted as reflecting a possible depletion of stored plant reserves or soil nutrients, so that sustained vegetative growth was constrained, while investment in reproduction was a secondary response reflecting increased production of flower buds in seasons prior to flowering (flower buds form one to several seasons prior to flowering in many tundra plant species : Sørensen 1941;Diggle 1997).…”
Section: Communitiesmentioning
confidence: 99%
“…An extreme example is provided by the common developmental pattern known as preformation, the initiation of determinate structures (e.g., leaves, inflorescences, flowers) one or more growing seasons prior to their complete maturation and function (Halle´et al, 1978;Diggle, 1997a). As a result of this prolonged period of development (potentially spanning portions of at least 2 years), responses to environmental variation may be delayed significantly (Diggle, 1997a;Aydellote and Diggle, 1997;Geber et al, 1997). Preformation is common among temperate trees, shrubs and herbaceous perennials and is nearly ubiquitous among taxa of the arctic and alpine tundra (reviewed by Sørensen, 1941;Diggle, 1997a).…”
Section: Developmental Limits To Morphological Plasticitymentioning
confidence: 99%
“…As a result of this prolonged period of development (potentially spanning portions of at least 2 years), responses to environmental variation may be delayed significantly (Diggle, 1997a;Aydellote and Diggle, 1997;Geber et al, 1997). Preformation is common among temperate trees, shrubs and herbaceous perennials and is nearly ubiquitous among taxa of the arctic and alpine tundra (reviewed by Sørensen, 1941;Diggle, 1997a). In Polygonum viviparum (Polygonaceae), a common component of many arctic and alpine plant communities, development of leaves and inflorescences requires 4 years from initiation to maturation (Diggle, 1997a).…”
Section: Developmental Limits To Morphological Plasticitymentioning
confidence: 99%
See 1 more Smart Citation